Organosiloxane-Modified Auricularia Polysaccharide (Si-AP): Improved High-Temperature Resistance and Lubrication Performance in WBDFs - Zhang, Fan; Wang, Yu; Wang, Bo; Geng, Yuan; Chang, Xiaofeng; Zhang, Wenzhe; Li, Yutong; Zhang, Wangyuan (Molecules (Basel, Switzerland), 2024)
This study introduces a novel organosilicon-modified polysaccharide (Si-AP) synthesized via grafting and comprehensively evaluates its performance in water-based drilling fluids (WBDFs). The molecular structure of Si-AP was characterized using Fourier-transform infrared spectroscopy (FTIR) and 1H-NMR experiments. Thermalgravimetric analysis (TGA) confirmed the good thermal stability of Si-AP up to 235 °C. Si-AP significantly improves the rheological properties and fluid loss performance of WBDFs. With increasing Si-AP concentration, system viscosity increases, API filtration rate decreases, clay expansion is inhibited, and drilling cuttings hydration dispersion is suppressed, especially under high-temperature conditions. Additionally, mechanistic analysis indicates that the introduction of siloxane groups can effectively inhibit the thermal degradation of AP chains and enhance their high-temperature resistance. Si-AP can form a lubricating film by adsorbing on the surface of clay particles, improving mud cake quality, reducing the friction coefficient, and significantly enhancing the lubricating performance of WBDFs. Overall, Si-AP exhibits a higher temperature-resistance limit compared to AP and more effectively optimizes the lubrication, inhibition, and control of the filtration rate of WBDFs under high-temperature conditions. While meeting the requirements of drilling fluid systems under high temperatures, Si-AP also addresses environmental concerns and holds promise as an efficient solution for the exploitation of deep-seated oil and gas resources.